THU0225 The Induction of Antinuclear Antibodies in Spondyloarthritis Patients Under Anti-TNF Alpha: A New Outcome Predictor?. (9th June 2015) - Fonseca, R.; Vieira, R.; Madureira, P.; Rosa-Gonçalves, D.; Aguiar, F.; Rocha, T.; Bernardo, A.; Mariz, E.; Bernardes, M.; Costa, L.
Abstract : Background: The induction of auto-antibodies, such as anti-nuclear antibodies (ANA), is a well-known phenomenon during anti-TNF alpha treatment. However, the correlation of this increase in ANA production and clinical response to anti-TNFα in Spondyloarthritis (Spa) patients is not yet determined. Objectives: To determine the impact of positivity for ANA (at baseline and after treatment) in clinical response and persistency of anti-TNFα treatment in Spa patients. Methods: Observational retrospective cohort study was performed. Patients fulfilling ASAS criteria for axial Spa, who started their first anti-TNFα between 2002 and 2013, and had performed serial ANA testing, were included. Disease activity (assessed with Bath Ankylosing Spondylitis Disease Activity - BASDAI and Ankylosing Spondylitis Disease Activity Score - ASDAS), clinical response (evaluated by ASDAS) and ANA testing (cut off titter >1/100) were collected at baseline and 6, 12, 18, 24 months (M) and in the last visit. Data were obtained by consulting Rheumatic Diseases Portuguese Register - Reuma.pt. Statistical analyses were performed using t-test, Mann-Whitney U-test, Chi-square and McNemar test (SPSS 21.0). Results: Among 129 Spa patients treated with anti-TNFα in our department, 104 patients (62.5% male, mean age 44.9 years (SD 11.6)) were included. The median follow-up time for this cohort was 3 years [1-11.5]. At baseline, ANA were detected in only 4 patients (3.8%). Disease activity parameters (BASDAI and ASDAS), ASDAS response or global drug discontinuation rate were similar between ANA positive and ANA negative patients at baseline. We found a seroconversion rate for ANA of 45.2% (n=47) with median time of 22 months [0-86]. Infliximab group demonstrated higher ANA seroconversion rate (66.7%, n=18) compared with adalimumab (46.5% n=20), etanercept (33.3%, n=7) and golimumab (15.4% n=2) (p=0, 012). The patients that had increased ANA after treatment showed smaller median changes in BASDAI at 18M (2.2 vs 3.75, p=0.036) and at 24M (2.45 vs 3.9, p=0.04). The changes in ASDAS, in absolute value, were also smaller at 18 and 24 M (1.4 vs 2.2, p=0, 023 and 1.8 vs 2.2, p=0.04 respectively) in these patients. No statistically significant differences were observed in ASDAS response at 6 and 12M. However, at 18M and 24M after treatment there was a higher rate of non-response in ANA positive patients (42, 4% vs 22, 5% p=0.027 and 36, 8% vs 13, 8% p=0.01 respectively). No significant differences in drug discontinuation rate due to al causes were found, between the two groups. Conclusions: We found a meaningful ANA seroconversion in Spa patients after anti-TNFα treatment. This study suggests that the increase of ANA after anti-TNFα treatment in Spa patients may affect clinical response with worse outcomes. Disclosure of Interest: None declared